The metamorphosis of economic theory under the hegemony of neoliberal doctrine: the influence of academia and its consequences - González Sarro, Iván (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
The text comments on the adjustment and accommodation to the theoretical foundations of the «single thought» that has been produced in the economic discipline, as a social science, during the hegemony of the neoliberal doctrine since 1973. It could be said that the postulates of neoliberal thought, in some way, have colonized the social sciences in general, and particularly the economic doctrine. It is explained how in this process the academy has had a relevant role, since neoliberal logic has also progressively been introduced and consolidated in the university environment –main bastion of the academy–, acquiring a global dimension. The consequences of all this are analyzed, linked to the «commodification» of higher education, to the idea of university education with a merely «professional» orientation and, therefore, devoid of any transformative concern, to the absence of critical thinking and the exploration of «other possible worlds», among others.
Keywords: Transformation of economic theory; neoliberal doctrine; commercialization of education; social sciences; critical thinking